Optimizing Understanding of Chicken Slaughter and Its Management for Traders: Realizing Islamic Sharia-Based Business Practices in West Aceh: Optimalisasi Pemahaman Penyembelihan Ayam dan Pengelolaannya bagi Pedagang: Mewujudkan Praktik Bisnis Berbasis Syariat Islam di Aceh Barat - Luthfi; Riza Hasan; Hilma Erliana; Rahmad Nuthihar; Intan Wulan Sari; Farthur Ahkyat; Hasnita; Ade Dwinta (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
This community service program aims to enhance the understanding of poultry traders in West Aceh regarding slaughter procedures in accordance with Islamic law (Sharia). The implementation methods include interactive educational workshops, socialization, and direct assistance to traders. The workshops discuss the importance of halal slaughter and Sharia-compliant business management, supported by expert speakers from the Department of Islamic Sharia. In addition to theoretical learning, traders are also involved in hands-on slaughtering practices to ensure proper implementation. Evaluation and monitoring are conducted to measure the traders' improved understanding, with a focus on the sustainability of the practices taught. This program has produced several important outcomes, such as increased trader knowledge, training certification, and additional facilities to support their businesses. The positive impact is felt not only by the traders but also by consumers who are more confident in the halal status of poultry products. Discussion sessions allow participants to share experiences and provide suggestions for further training, including the slaughtering of other animals such as goats and buffaloes. This program contributes to the improvement of Sharia-based business quality in West Aceh and strengthens consumer trust in products that meet halal standards. Support from various parties, including the government and the community, reinforces the success of this program.